Teologi Sistematika Dalam Membangun Ekklesiologi Multikultural Di Indonesia - Harefa, Febriaman Lalaziduhu (Sekolah Tinggi Teologi Sriwijaya, 2024)
This research aims to describe the principles of systematic theology in building an ecclesiological model that embraces cultural diversity within the context of the church in Indonesia. The background of this study is the reality of cultural, ethnic, and religious diversity in Indonesia, which often presents challenges for the church in maintaining unity and harmony. The research method employed is literature study, collecting and analyzing sources related to ecclesiology and multiculturalism. The findings indicate that principles of systematic theology, such as anthropological, cosmological, Christ's incarnation, God's sovereignty, and missiological aspects, can be applied to develop an inclusive, just, and contextual multicultural ecclesiological model. The conclusion of this research emphasizes that systematic theology plays a crucial role in creating a church that values diversity, promotes unity, and remains relevant in the multicultural context of Indonesia.